Post-release evaluation of Megamelus scutellaris Berg. (hemiptera: delphacidae): a biological control agent of water hyacinth Eichhornia crassipes (Mart.) Solms-Laub (Pontederiaceae) in South Africa - Miller, Benjamin Erich (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
Water hyacinth, Eichhornia crassipes (Mart.) Solms-Laub. (Pontederiaceae) is a free-floating aquatic macrophyte from South America that was introduced to South Africa in the 1900s for its attractive ornamental flowers. The plant was classified as a serious invader in the country in the 1970s, eventually becoming the worst invasive aquatic plant in South Africa. Biological control is widely regarded as the most effective method of managing water hyacinth, as it is ecologically safe, cost-effective, and self-sustaining. To date, nine biological control agents have been released in South Africa against water hyacinth, including eight arthropods and a pathogen. Due to the cumulative effects of highly eutrophic waterbodies, which mitigate the damage caused by biological control, and the cold winters which inhibit the rate of biological control agent population build up, South Africa currently has more biological control agents released on water hyacinth than anywhere else in the world. The need for a cold-tolerant agent that can reproduce and develop quickly, while still being damaging to water hyacinth in eutrophic systems, led to the introduction of the most recently released water hyacinth biological control agent, the planthopper Megamelus scutellaris Berg (Hemiptera: Delphacidae), which was initially collected from Argentina. This thesis formed the first post-release evaluation of M. scutellaris since its release in South Africa in 2013. It included a greenhouse experiment to measure the agent's feeding damage in relation to different nutrient levels and stocking rates, as well as a field component to evaluate both the post-winter recovery of M. scutellaris, and a nationwide survey to measure the establishment of the agent around the country in relation to climate, water quality, and plant health. In the greenhouse experiment, the feeding damage was quantified using measurements of plant growth parameters and chlorophyll fluorometry. It was found that, like other biological control agents of water hyacinth, M. scutellaris was most damaging when released in high numbers on plants grown at medium nutrient levels, and less effective on plants grown at elevated nutrient levels. A water hyacinth infestation on the Kubusi River was selected for the evaluation of the post-winter recovery of M. scutellaris. The Kubusi River is both the first site where M. scutellaris was released, and the coldest site where water hyacinth biological control agents have established successfully in South Africa. Monthly visits tracking seasonal plant health characteristics and agent population densities indicated that the populations of M. scutellaris were impacted most significantly by the season. Low temperatures led to the water hyacinth plants being of poor quality during the winter, which had a subsequent negative effect on the agent populations. The agents could only fully recover by late summer, which meant that the plants were without any significant biological control through the initial phases of the growing season, when they were most vulnerable, and a significant lag-phase occurred between the recovery of the plants and the recovery of the agent population after the winter bottleneck. A survey of all sites where M. scutellaris had been released in South Africa yielded 16 sites where the agents had successfully established, having survived at least one full winter. Among these sites were four sites where the agents were found without them having been released, indicating that they can disperse unaided to new sites. The temperature was a major factor responsible for the success or failure of establishment, with very few agents surviving in the hot areas of South Africa or in areas with a high frost incidence. The density of M. scutellaris was higher in nutrient-rich water, and on plants with more leaves, suggesting that the quality of the plants also contributed to establishment. The results of this thesis showed that M. scutellaris is able to establish successfully in South Africa, and that the agents are capable of causing significant damage to water hyacinth, making it a promising addition to the biological control programme. Novel methods of measuring subtle insect feeding damage in plants and quantifying agent populations are also discussed, along with suggestions for the future implementation of M. scutellaris in South Africa.
Keywords: Megamelus scutellaris Berg.; Delphacidae; Noxious weeds -- Biological control -- South Africa; Aquatic weeds -- Biological control -- South Africa; Water hyacinth -- Biological control -- South Africa; Biological pest control agents